ASSESSMENT OF GENDERS DIFFERENCE IN SKILLS USED BY STUDENTS’ ON PRACTICAL ATTACHMENT FOR EFFECTIVE MANAGEMENT OF ADULT LEARNING CENTRES IN NIGERIA - MAHMUD, Abbas; DANKANI, MURJA BELLO (Sokoto Educational Review, 2023)
The study aimed to assess Gender Differences in Skills Utilized by Students during Practical Attachment for the Effective Management of Adult Learning Centers in Nigeria. It was guided by three hypotheses and sought to identify the skills employed by students in facilitating learning for adult learners during practical attachments and to determine the management strategies implemented by students in controlling the learning centers where they were placed. The research included addressing three specific questions and testing four hypotheses. Employing a Descriptive Survey research design, the study involved a population of 93 students in the Adult Education program during the 2018/2019 academic session. The sample size coincided with the population count, and the sampling method employed was purposive. The study relied on a self-designed instrument for data collection. Analysis was conducted using Descriptive Statistics, and the hypotheses were evaluated using the Pearson Product Moment Correlation (PPMC). The findings from the three hypotheses indicated that there was no significant difference between male and female students concerning the skills utilized during practical attachments or the strategies employed to manage adult learning centers in the context of practical attachments. The study's conclusions highlighted the absence of significant differences between male and female students concerning the skills, management strategies, and learned theories applied while facilitating adult learning in various adult learning centers during practical attachments.